1984
DOI: 10.1042/bj2190041
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal antioxidant defence in some tissues of congenitally obese mice

Abstract: The concentration of lipoperoxides (estimated as thiobarbituric acid-reactive material) and some components of the antioxidant defence system have been compared in various tissues of lean and congenitally obese mice. NADPH-stimulated lipoperoxide generation in vitro was significantly higher in microsomes (microsomal fractions) prepared from obese hepatic tissue than lean. Plasma, liver and brain lipoperoxide concentration was significantly higher in obese mice. In blood derived from obese mice the concentratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
24
0
1

Year Published

1986
1986
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 48 publications
3
24
0
1
Order By: Relevance
“…Capel and Dorell demonstrated that ob/ob mice compared with wild type mice had reduced levels of hepatic GPx and GSH [1]. Consistent with this observation, Park et al, showed that high-fat diet-induced obese mice also had lower hepatic GSH level [14].…”
Section: Resultssupporting
confidence: 70%
See 1 more Smart Citation
“…Capel and Dorell demonstrated that ob/ob mice compared with wild type mice had reduced levels of hepatic GPx and GSH [1]. Consistent with this observation, Park et al, showed that high-fat diet-induced obese mice also had lower hepatic GSH level [14].…”
Section: Resultssupporting
confidence: 70%
“…Mutant mice that cannot produce the appetite-suppressing hormone leptin (ob/ob mice) eat to the point of extreme obesity. These mice, as well as high-fat diet-induced obese mice, generate high amounts of ROS and demonstrate increased hepatic lipid peroxidation compared with healthy wild type mice [1,4,8,23]. As such, ob/ob mice were employed in the current study to explore the impact of Jeju ground water on the hepatic antioxidant system.…”
Section: Introductionmentioning
confidence: 99%
“…NAC was tried because reduced levels of GSH have been observed in animal models of NASH. 38,39 NAC increases the availability of intracellular GSH through the provision of cysteine for GSH biosynthesis and acting as an antioxidant molecule by itself. 40,41 In our hands, NAC both restored the intracellular pool of GSH and increased catalase-like activity in the livers of ob/ob animals to higher levels than those observed in control lean littermates.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, liver GPX was reported to be decreased in a previous study on ob/ob mice [7,8], but the CAT activity was not determined in those studies. The CuZnSOD was unaltered in the present obese liver.…”
Section: Discussionmentioning
confidence: 95%
“…Thus, study of the oxidant-antioxidant balance in obesity is of clinical importance. However, little is known about the oxidantantioxidant status in obesity, and data are limited to the genetically obese ob/ob mouse [6][7][8][9]. Abnormal metabolism of trace metals, which is not directly linked to excessive weight gain, is reported to exist in the ob/ob mouse [10].…”
Section: Discussionmentioning
confidence: 99%